Da expansão urbana às transfigurações socioambientais: risco e vulnerabilidade em Feira de Santana, Bahia - Dias, Laerte Freitas (2023)
Flood and waterlogging episodes have become increasingly common in urban contexts. Far from being purely natural factors, such recurrences reflect the degree of social interference in space, resulting from the dichotomous vision applied to environmental issues combined with fragmented and unequal actions in the appropriation of urban land. Social exposure to environmental hazards reveals the production of spaces endowed with vulnerabilities and risks. This increases the potential for disasters, making the impacts visible amidst the occupation of environmentally fragile places. Using analytical concepts from Geography, the thesis aims to analyze socio-environmental risk and vulnerability to floods in the urban expansion of Feira de Santana-BA. Based on this premise, the following specific objectives were outlined: to understand the advancement of the urban fabric on the natural system; to configure the climatic aspects and the historical duality of living with droughts and floods; to evaluate biophysical conditioning and susceptibility to urban floods; to characterize vulnerable places and social groups. The study is justified by the processes of flooding and waterlogging in a semi-arid context due to the unequal appropriation of urban space and unsustainable actions of domination of nature. Methodologically, it involves a literature review, collection of secondary data from official agencies, use of historical sources (printed newspapers and electronic media), digital processing of satellite images, and creation of a database in a GIS environment. In addition to these, there are field records, both in dry and rainy periods, in order to validate the generated products and describe the socio-environmental configurations. It was observed that Feira de Santana is in full process of expanding the urban footprint, with the persistence of actions that disregard the natural system, prevailing the interests of real estate agents in the constitution of the city. Social exposure to floods permeates through the production of the city, through the unequal use of urban space, the advancement of the process of soil sealing, and unrestricted occupation of water bodies, especially lagoons. Therefore, disaster episodes are correlated with social intervention in the constitution of space, particularly by disregarding natural conditioning factors. Based on data on biophysical susceptibility to floods and social vulnerability, points of greater risk were identified. The neighborhoods of Novo Horizonte, Campo Limpo, Estação Nova, Lagoa Salgada, Baraúnas, and Queimadinha stand out, especially due to the social deprivation in responding to disaster contexts. The overlap of the problem is emphasized, as the magnitude of certain vulnerability can lead to the persistence and appearance of others, thus inserting flooding into the context of hybrid risks. In areas directed towards urban expansion, according to the Master Plan, locations susceptible to floods were identified, but of lower risk given the degree of occupation. This fact points to the need to formulate and implement planning actions capable of considering the biophysical system along with the accelerated advancement of the urban footprint.